Vocational situation and experiences from the work environment among individuals with neuromuscular diseases. - Lexell, E. M.; Langdell, I.; Lexell, J. (Work, 2017)
BACKGROUND: Neuromuscular diseases (NMD) can affect the ability to be employed and to work, but there is limited knowledge of individuals' own perspectives of factors that are important for their vocational situation. OBJECTIVE: To explore the vocational situation among people with NMD that are employed, and to describe their experiences of how their disability, personal and environmental factors influence their ability to continue to work. METHODS: Nine participants with different NMD were included. A mixed-methods design was used, and data were collected by means of semi-structured and open-ended interviews, and ratings of aspects supporting or interfering with their work performance and the ability to continue to work. Data were analyzed with directed content analysis based on the International Classification of Functioning, Disability and Health, and with descriptive statistics. RESULTS: The participants' personal characteristics, support from others at work and at home, and a flexible work organization were perceived as important factors facilitating work continuation, whereas physically demanding work assignments and factors in the physical environment were perceived as barriers. CONCLUSIONS: Knowledge of how personal characteristics as well as support from the work organization, managers and family members can facilitate the ability to work is important for employers, staff within different parts of the health care system, and the social security system. Future research should focus on interventions that are best suited to enhance the vocational situation for individuals with NMD.